EFL Students' Attitude Toward Learning English - Meul - Isti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
Abstract: The purpose of this research was to analyze EFL students’ attitude toward learning English based on three aspects namely affective, cognitive and behaviour and to find out factors shaping students’ attittude. This research was conducted in a public junior high school in district Sokaraja. This research belongs to survey study in which the researcher took 30% from population as the samples. The researcher chose 7th grade students to get involved as the participants. In order to answer the research questions, three instruments were used. Those were questionnaire, interview guide, and note taking of observation. Based on the result of the study, students had possitive attitude in those overall aspects. However, the behavioural aspect comes first accounting for 68,8% followed by affective aspect accounting for 68,10%. Those were higher compare to cognitive aspect which was accounted for just 64,7%. Then it was supported by the results of observation and interview in some points of each aspect. In addition, the result of questionnaire and interview displayed six factors affecting students’ attitude: mass media, refference group, teacher, personal experience, parents and the last is learning climates and classroom task. Some results of factors shapping students’ attitude were also supported by the interview.